Regnum og sacerdotium i en Saxo-disputats - og hos Saxo - Breengaard, Carsten; Skovgaard-Petersen, Inge (Kirkehistoriske Samlinger, 1988)
Summary - af Carsten Breengaard The article by Carsten Breengaard undertakes a critical analysis of the regnum-sacerdotium problem complex, as treated in the thesis by Inge Skovgaard-Petersen »Da Tidernes Herre var nær. Studier i Saxos historiesyn«, 1987. For most of this century the interpretation of Saxo have been determined by Curt Weibull’s rejection of Saxo’s value as a narrative source (Saxo. Kritiska undersökninger i Danmarks historia från Sven Estridsens död till Knut VI. 1915), and by Lauritz Weibull’s decision that Saxo tended towards anti-Gregorianism (Nekrologierna från Lund, Roskildekrönikan och Saxo. Grunddrag i Danmarks historia under det 12. århundradet. Scandia 1928). It is demonstrated in the article that Inge Skovgaard-Petersen is still working within the Weibullian universe, and that this leads to a succession of misinterpretations of Saxo. In her treatment of Saxo’s representations of the third, fifth and sixth decades of the 12th century, Inge Skovgaard-Petersen incorporates Weibullian problem complexes for which there is no justification. It is demonstrated that Saxo has no interest in emphasizing regnum at the expense of sacerdotium. The endeavour of Saxo’s work is to safeguard his Christian native land - Denmark - against the maladministration of the great families. Furthermore, Carsten Breengaard proves in his article that on certain points it is not clear whether Inge Skovgaard-Petersen is working as a historian or as a literary historian. Summary - af Inge Skovgaard-Petersen Inge Skovgaard-Petersen grants Carsten Breengaard that she does not distinguish between historical research and literary analysis. But that is a crucial point in the thesis. She justifies her method through references to the works of literary analysis by Erich Auerbach and Northrop Frye. Inge Skovgaard-Petersen emphasizes that even though at times the historical criticism by the Weibull brothers was rather rigid, and though they concentrated on political history at the expence of social history, she readily admits being indebted to them.